Nitric Oxide-Mediated Maize Root Apex Responses to Nitrate are Regulated by Auxin and Strigolactones - Manoli, Alessandro; Trevisan, Sara; Voigt, Boris; Yokawa, Ken; Baluška, František; Quaggiotti, Silvia (Frontiers in Plant Science, 2016)
Nitrate (NO3-) is a key element for crop production but its levels in agricultural soils are limited. Plants have developed mechanisms to cope with these NO3- fluctuations based on sensing nitrate at the root apex. Particularly, the transition zone (TZ) of root apex has been suggested as a signalling-response zone. This study dissects cellular and molecular mechanisms underlying NO3- resupply effects on primary root growth in maize, confirming nitric oxide (NO) as a putative modulator. Nitrate restoration induced primary root elongation within the first 2 h, corresponding to a stimulation of cell elongation at the basal border of the TZ. Xyloglucans (XGs) immunolocalization together with Brefeldin A applications demonstrated that nitrate resupply induces XG accumulation. This effect was blocked by cPTIO (NO scavenger). Transcriptional analysis of ZmXET1 confirmed the stimulatory effect of nitrate on XGs accumulation in cells of the TZ. Immunolocalization analyses revealed a positive effect of nitrate resupply on auxin and PIN1 accumulation, but a transcriptional regulation of auxin biosynthesis/transport/signalling genes was excluded. Short-term nitrate treatment repressed the transcription of genes involved in strigolactones (SLs) biosynthesis and transport, mainly in the TZ. Enhancement of carotenoid cleavage dioxygenases (CCDs) transcription in presence of cPTIO indicated endogenous NO as a negative modulator of CCDs activity. Finally, treatment with the SLs-biosynthesis inhibitor (TIS108) restored the root growth in the nitrate-starved seedlings. Present report suggests that the NO-mediated root apex responses to nitrate are accomplished in cells of the TZ via integrative actions of auxin, NO and SLs.